Desigualdades y justicia social: informe Desigualdades en México 2018 - Ugalde, Vicente (El Colegio de México A.C., 2018)
At a time when it is difficult to escape the discourse of “evidence-based policies” and in an environment marked by the end of electoral campaigns, and therefore a certain saturation of messages in the public space, El Colegio de México presented the Inequalities in Mexico 2018 report in June 2018. Although it does not contain policy recommendations, the report is expressly designed to promote public discussion and examine “the candidates' platforms in the 2018 presidential elections”. Drawn from studies which, for some time now and in various scientific disciplines, researchers at this center of education and research have produced, the report constitutes a sort of white paper with specific expressions of inequality in Mexico between 2000 and 2017, thereby providing a broad, ambitious diagnosis of this social problem.